A graph approach to generate all possible regression submodels - Gatu, Cristian; Yanev, Petko I.; Kontoghiorghes, Erricos John (My University, 2007)
A regression graph to enumerate and evaluate all possible subset regression models is introduced. The graph is a generalization of a regression tree. All the spanning trees of the graph are minimum spanning trees and provide an optimal computational procedure for generating all possible submodels. Each minimum spanning tree has a different structure and characteristics. An adaptation of a branch-and-bound algorithm which computes the best-subset models using the regression graph framework is proposed. Experimental results and comparison with an existing method based on a regression tree are presented and discussed.
Keywords: Regression analysis; Algorithms; Branch-and-bound algorithm; Computer simulation; Set theory